Analysis of Learning Enthusiasm Evaluation Through Group Investigation in Learning Quality - Eka Anggis; Andang Syaifuddin (At-Taqaddum, 2021)
The Group Investigation model is a cooperative model to develop an enthusiasm for learning. Problems in the field from interviews with students of SMP 1 Indramayu were found to be as follows: lack of group collaboration, less responsiveness, lack of attention, sleepiness so that it can be concluded that there is a lack of enthusiasm for students in learning. The purpose of this research is to analyze the indicators of the most dominant learning enthusiasm if learning is carried out through Group Investigation to solve problems in the places observed. The research method is descriptive qualitative analysis. A questionnaire instrument measured the four indicators. The subject of the research is class VIII Middle School 1 Indramayu. Data collection techniques are data collection, data presentation, conclusions. The results show that from the four indicators of enthusiasm, the indicator that got the highest percentage (83%) was students' enthusiasm in noting important things as teaching materials at home. The conclusion of the enthusiasm indicator in the form of student learning enthusiasm in recording important things is the most dominant when learning is implemented through Group Investigation. Thus, it is necessary to improve learning through group discussions in the future.